CURRENT METHODS OF CHEESE ENRICHMENT WITH CALCIUM SALTS - A. G. Khramtsov; V. A. Dinyakov; A. D. Lodygin (Современная наука и инновации, 2022)
The problems of the increase in the incidence of osteoporosis among the population of the Russian Federation and the search for an effective solution to it are considered. The relevance of the use of dairy products for the prevention of osteoporosis is substantiated. The purpose of the research is to compare the implemented domestic and foreign scientific and technical developments and technological methods of cheeses enrichment with calcium salts. A scientifically based description of each of the studied methods is presented. Based on the analysis of information sources, the expediency of this functional dairy products group manufacturing has been confirmed. The forecast of the production of dairy products enriched with vitamins and minerals is made. The relevance of dairy products application for osteoporosis prophylaxis is grounded. Domestic and foreign scientific and technical developments and technological methods of cheese enrichment with calcium salts are considered. The expediency of this functional dairy products group production is proved.